Peran Digitalisasi dalam Meningkatkan Layanan Nasabah Pada Bank BRI KC Surabaya Kertajaya - Ida Ayu Nuh Kartini; Dianizar El Ghifary; Bima Wahyu Luckyta; Titis Elvina Indriyani; Nandathia Intan Sunur (Yayasan Daarul Huda Kruengmane, 2025)
Digitalization in banking services has also influenced how customers access information and conduct transactions. Research by Ginanjar and Pasaribu highlights the impact of e-banking facilities and social media in building customer satisfaction and loyalty. In this context, the use of social media as a communication and promotional tool is highly relevant for banks to reach a broader customer base and meet their needs in real time. Bank BRI KC Surabaya Kertajaya has positioned the BRImo application as the core of its digital customer service transformation. This effort focuses not only on technological development but also on customer empowerment through tailored educational programs, particularly for those who are less familiar with the digital environment. The objective is to ensure that every customer, without exception, can experience the convenience and benefits offered by digital banking services. The implementation of digitalization through BRImo has had a significant impact on customer satisfaction. Improved accessibility, an attractive application user interface, and comprehensive features have enhanced the overall customer experience. This demonstrates that investment in digital technology, when executed effectively, can lead to significant improvements in service quality and customer loyalty.